Subjective work experiences, career orientations, and psychological career resources of working adults - Coetzee, Melinde; Schreuder, Dries (South African Journal of Higher Education, 2016)
The primary objective of the present study was to assess whether career orientations and psychological career resources relate to individuals’ subjective work experiences. A quantitative survey was conducted on a random sample of 2 997 participants at predominantly managerial and supervisory level in the South African service industry. The measuring instruments consisted of a subjective work experiences scale, the Career Orientations Inventory and Psychological Career Resources Inventory. The results indicated career orientations and psychological career resources as significant predictors of the participants’ subjective work experiences. The results make an important contribution to existing literature on career well-being and subjective career success. Key words: career orientations; psychological career resources; life satisfaction; job/career satisfaction; happiness; work as valuable activity